The First Interchangeable Biosimilar Insulin: Insulin Glargine-yfgn. (March 2023) - Matli, Mark C.; Wilson, Andrea B.; Rappsilber, Leah M.; Sheffield, Farron P.; Farlow, Miranda L.; Johnson, Jeremy L.
On March 23, 2020, all insulin products were reclassified as biologics instead of drugs under the Biological Price Competition and Innovation (BPCI) Act of 2009. This allows biosimilar insulin products to be manufactured when the patent expires for the reference biologic, sometimes called the originator or brand name product. A biosimilar product may not be substituted for the reference biologic at the pharmacy counter unless the biosimilar undergoes further switch trials to earn the designation as an interchangeable biosimilar. Insulin glargine-yfgn 100 units/mL is the first biosimilar insulin to attain interchangeable status with the reference insulin glargine. In the INSTRIDE 1 and INSTRIDE 2 trials, insulin glargine-yfgn has proven noninferiority regarding blood glucose reduction and adverse effect profile versus reference insulin glargine; even in the INSTRIDE 3 trial in which treatment of diabetes was switched between insulin glargine-yfgn and reference insulin glargine throughout the trial without statistically significant changes to glucose levels or adverse effects. Insulin glargine-yfgn may be substituted at the pharmacy counter without consultation with the prescriber, in accordance with state laws. In suit with other biosimilars, insulin glargine-yfgn's list price is significantly lower than other insulin glargine products. This increases market competition leading to decreases in costs of other insulin glargine products. Many patients who could not previously afford insulin therapy may now have significantly improved access to treatment. Providers will need education to increase awareness of these new biosimilars and interchangeable biosimilar insulin products, cost benefits, and substitution allowances.